Degrees of Intersectionality : Male Rap Artists in Sweden Negotiating Class, Race and Gender - Berggren, Kalle (My University, 2013)
“Intersectionality” has become a highly influential concept in gender research over the last 25 years. Debates have focused on differences and power asymmetries between women, in terms of race but also addressing class, age, sexuality, ability and nation. However, intersectional paradigms have been used to a much lesser extent in gender studies on men. This article seeks to contribute to an emerging discussion about intersectionality and masculinity by analyzing rap lyrics in Swedish songs. The data consists of a broad sample of rap lyrics by male artists 1991-2011, which is analyzed through poststructuralist discourse analysis and queer phenomenology. The analysis shows how classed discourses can be described in terms of orientation and flow, how racialization is articulated in terms of place, and the role of normative notions of gender and sexuality in anti-racist discourses. It is argued that this interconnectedness – class being related to race, which in turn is profoundly gendered – is neither well captured by the prevailing notion of “masculinities” in gender studies on men, nor by the “constitution” vs. “addition” dichotomy in intersectionality debates. Instead, it is suggested that degrees of intersectionality might be a more fruitful way of theorizing intersectionality in rela-tion to men.
Keywords: 306 Kultur und Institutionen; intersectionality; hip hop; rap lyrics; men and masculinities; racialization; class; queer phenomenology; Sweden